Identification of a novel nucleotide-sensitive microtubule-binding protein in HeLa cells (The Rockefeller University Press, 1990)
A protein of Mr 170,000 (170K protein) has been identified in HeLa cells, using an antiserum raised against HeLa nucleotide-sensitive microtubule-binding proteins. Affinity-purified antibodies specific for this 170K polypeptide were used for its characterization. In vitro sedimentation of the 170K protein with taxol microtubules polymerized from HeLa high-speed supernatant is enhanced in the presence of an ATP depleting system, but unaffected by the non-hydrolyzable ATP analogue AMP-PNP. In addition, it can be eluted from taxol microtubules by ATP or GTP, as well as NaCl. Thus it shows microtubule-binding characteristics distinct from those of the previously described classes of nucleotide-sensitive microtubule-binding proteins, the motor proteins kinesin and cytoplasmic dynein, homologues of which are also present in HeLa cells. The 170K protein sediments on sucrose gradients at approximately 6S, separate from kinesin (9.5S) and cytoplasmic dynein (20S), further indicating that it is not associated with these motor proteins. Immunofluorescence localization of the 170K protein shows a patchy distribution in interphase HeLa cells, often organized into linear arrays that correlate with microtubules. However, not all microtubules are labeled, and there is a significant accumulation of antigen at the peripheral ends of microtubules. In mitotic cells, 170K labeling is found in the spindle, but there is also dotty labeling in the cytoplasm. After depolymerization of microtubules by nocodazole, the staining pattern is also patchy but not organized in linear arrays, suggesting that the protein may be able to associate with other intracellular structures as well as microtubules. In vinblastine- treated cells, there is strong labeling of tubulin paracrystals, and random microtubules induced in vivo by taxol are also labeled by the antibodies. These immunofluorescence labeling patterns are stable to extraction of cells with Triton X-100 before fixation, further suggesting an association of the protein with cytoplasmic structures. In vivo, therefore, the 170K protein appears to be associated with a subset of microtubules at discrete sites. Its in vitro behavior suggests that it belongs to a novel class of nucleotide-sensitive microtubule-binding proteins.